Perception of sexual abuse in school children - Elizalde Bravo, Roger (1999)
This study explorer the problem of the sexual abuse in 391 scholars of sex both, proceeding of centers state educative of primary level, of socioeconomic stratum short and of wich ages to fluctuate between the 7 or 14 ages. Initialy be constructed a questionary of 32 items and chip sociodemographic for to determínate the characterístics of the sample. Be to find different significative in function to sex the boys to considerate ages of rísk or abuse sex between 3 or 5 ages, and the girls the ages of 8 or 11 ages. Existence greaters fears and preocupaty in the girls of to be victims and elk cualquier sex persecute preference communicative or the mother before who or the father. In general the childs to present or high assessment and to estímate toward your body.